Pengaruh Kombinasi Kompres Dingin dan Teknik Distraksi Audiovisual Terhadap Tingkat Nyeri Saat Pemasangan Infus Pada Anak Usia Sekolah - Anita Putri; Nur Eni Lestari; Hari Ghanesia (Journal of Nursing Education and Practice, 2025)
Introduction: Pain during invasive procedures such as IV insertion in school-age children can lead to trauma and non-cooperative behavior. Non-pharmacological interventions like cold compresses and audiovisual distraction are recommended to reduce pain perception.   Objective: To determine the effect of the combination of cold compress and audiovisual distraction on pain levels during IV insertion in school-age children.   Methods: This research used a pre-experimental post-test only control group design with a total of 30 respondents divided into intervention and control groups. The sampling technique used was purposive sampling. The research instrument used to measure pain level was the Wong-Baker FACES Pain Rating Scale. Data were analyzed using the Mann–Whitney U test.   Results: The intervention group experienced significantly lower pain scores compared to the control group with a p-value = 0.018 (p < 0.05), indicating a statistically significant difference.   Conclusion: The combination of cold compress and audiovisual distraction is effective in reducing pain during IV insertion in children. The combination of cold compress and audiovisual distraction can be applied by nurses as a non-pharmacological intervention to reduce pain during invasive procedures in children. Furthermore, this intervention can be established as a Standard Operating Procedure (SOP) for pain management during IV insertion in pediatric care settings.